DESIGN OPTIMIZATION OF BREAD-BAKING OVEN CHAMBER: A COMPUTATIONAL FLUID DYNAMICS (CFD) APPROACH TO THE TEMPERATURE DISTRIBUTION - Sektiono, Moch. Wisnu Arif; Wahyu, Mujahid; Halimi, Ahmad Dzulfikri; Hendarti , Devina Rosa; Cahyono, Hiding (Jurnal Rekayasa Mesin, 2025)
This paper presents a Computational Fluid Dynamics (CFD) simulation of a bread oven under steady-state conditions. An experimental measurement methodology was performed to determine the temperature distribution characteristics in the oven chamber. The CFD model simulation of the bread oven shows a homogeneous temperature distribution. Using a numerical model validated against experimental measurements, it is possible to highlight the temperature distribution pattern in the oven chamber and understand how the temperature spreads in a conductive air medium. Using data from experimental tests and CFD simulations, observations were made on temperature variations for 100, 110 and 120 in the oven chamber. The temperature for the oven chamber is distributed for a homogeneous distribution, with the temperature being 120 °C in both measurement and simulation. The lowest flow velocity is ~ 1.1 m/s, which is indicated by the light blue colour on the oven rack, and the highest velocity is ~ 4 m/s.